Satisfação de pais de crianças deficientes auditivas quanto ao desenvolvimento auditivo e de linguagem: construindo indicadores de qualidade em um serviço de saúde auditiva - Fortes, Paula Couto (2009)
Introduction: Parental satisfaction with auditory and language development of their hearing impaired children can be an important factor in constructing quality indicators of intervention process. Goals: To describe and discuss parental satisfaction with auditory and language development of their hearing impaired children during the periodical follow up process within a high complexity service within the public health system, aiming at raising aspects related to quality indicators. Method: Twenty hearing impaired children less than three years of age, their parents and therapists participated in the study. All children were diagnosed and received their hearing aids at the Center for hearing in children CeAC, in the city of São Paulo. Data were collect using: children s files, an interview guide for parents, Questionnaire for satisfaction, and a parental involvement scale used by clinicians to assess the family. Results: Most parents were satisfied with auditory skills development, but not satisfied with language development. Hearing aids were the most recalled factor related to child s development. Length of time in intervention had a negative moderate relation with parental satisfaction with language development. Regarding the clinicians, the majority was satisfied with auditory skills of the children but was also not satisfied with language development. Hearing aids, intervention and family were the most recalled factor related to child s progress. Conclusion: Results indicate that there is a need to work with parents within the therapeutic process, regarding their hopes, needs and expectations regarding auditory and language development of their hearing impaired children